IMPLEMENTASI TEACHING AT THE RIGHT LEVEL (TARL) BERBASIS PROYEK TERHADAP HASIL DAN MOTIVASI BELAJAR PESERTA DIDIK PADA MATA PELAJARAN IPAS KELAS V SD - Komaria, Siti; Syahrani, Agus; Kusdaryati, Kusdaryati (FKIP Universitas Tanjungpura, 2025)
This study is a Classroom Action Research aimed at examining the implementation of Teaching at the Right Level (TaRL) approach based on Project Based Learning (PjBL) to improve the learning outcomes and motivation of 5th grade elementary school students. The research procedure follows Kurt Luwin’s model which includes 4 stages in each cycle such as (1) action planning, (2) action implementation, (3) observation, and (4) reflection and analysis. This research was conducted over 3 cycles in 5th grade – A at SD Negeri 24 Pontianak Kota that involving 29 students. The Instruments used include observation sheets of learning implementation, learning outcome tests, and learning motivation questionnaires. The results showe a significant improvement in both learning implementation and student learning outcomes. Learning implementation percentage increased from 85,71% in first cycle to 95,24% in second cycle and reached 100% in third cycle. Student score average also increased from 65,38 (62,07% mastery) in first cycle to 79,00 (89,66% mastery) in second cycle and reached 89,83 (100% mastery) in third cycle. Meanwhile, the overall analysis of student learning motivation reached an average of 88,90% categorized as very strong covering cognitive, conative, and affective aspect. These findings indicate that the PjBL based on TaRL approach successfully creates a more structured, engaging learning environment that hilistically fosters student’s enthusiasm and active participation in learning activity.